ARAT SABULUNGAN : STRATEGI DAN NEGOSIASI KULTURAL MINORITAS MUSLIM DI KEPULAUAN MENTAWAI - Eka Putra Wirman; Muhammad Ilham; Refinaldi (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
This article will describe the recruitment strategy for the younger generation segment and the cultural negotiation strategy of the Mentawai Muslim minority in the midst of local traditions. Practically, this paper contributes to friendly and negotiable models of Islamic cultural studies with local values. The research was conducted with a qualitative approach. Data were collected through observation, documentation, and interview techniques. Data analysis was carried out with reference to technical analysts Miles and Huberman. Arat Sabulungan as a local belief for the original Mentawai people, is an elementary value for the Mentawai people. The historical-political factors of the New Order era, sociologically, made the consistency of religious beliefs not smooth. In addition, this is also caused by cultural negotiations which in the Islamic concept are more "difficult" compared to non-Islamic ones. The practice of Arat Sabulungan is a variable that contributes to the difficulty of the cultural negotiation. The strategy used by Islamic preachers which has been considered successful so far is by way of syncretic da'wah and education. The younger generation is a “guarded group”.